Biological Fertilizer Giving Effect On The Growth And Results Of Two Plant Variety Of Soybean(Glycinemax L.) - Gunawan, Bambang (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2018)
Soy is a crop-producing substances essential for human food. The content of amino acids making up the protein and soy protein to replace animal protein needs of the people of Indonesia. But compliance is constrained by local soybean production is low. Local soybean production is able to meet only about 25% of the total requirement of tempeh and tofu industry, while 75% drawbacks to be imported from soybean producing countries. The purpose of this study was to determine the influence of factors such as a wide variety and concentration of biological fertilizers as well as the interaction of both factors on the growth and yield of soybean. Based on the research results, it can be concluded as follows: a. Combination treatment of varieties and biological fertilizers showed a significant interaction effect on stem diameter, number of pods per plant but did not show an interaction effect on plant height, leaf number and weight of seeds per plant. The best results were obtained in treatment combinations (V1H3)namely the combination treatment Anjasmoro varieties and concentrations of biological fertilizers 7 ml / liter of water. b. Varieties showed significant treatment effect on plant height, leaf number, stem diameter, number of pods per plant and seed weight per plant. Treatment Anjasmoro varieties (V1)show growth and higher yields than varieties baluran (V2). Biological fertilizer treatment showed no significant effect on plant height, but showed a significant influence on the amount of leaf and seed weight per plant, where the best results are achieved by treatment of H3. Keywords: soybean varieties, biological fertilizer.